PELAKSANAAN.LAYANAN.KONSELING KELOMPOK DALAM MENGATASI K€SULITAN.BELAJAR. - Fatmawati, Dewi; Mudaim, Mudaim; Muzni, Achmad Irfan (Universitas Muhammadiyah Metro, 2023)
The objectives of this study are 1) to determine the implementation of group counseling services in overcoming student’s learning difficultie. 2) to determine the preparation of group counseling service. 3) to determine the evaluation carried out by counselors on students. This research method uses qualitative research. The presence of researchers as research data collectors as well as analyzing the data of this research instrument using interview sheets, obsevation and documentation. Data analysis using descriptive data. The conclusion of this study isthe preparation of group counseling servies as an implementation to assist studentin overcoming learning diffculties,